Seedling emergence and yield performance of wheat cultivars depending on seed vigor and sowing density - Abati,Julia (2017)
Abstract: The use of high quality seeds, the appropriate management practices and the selection of promising genotypes are strategies to exploit the wheat yield potential. Thus, the goal of this study was to evaluate the effect of the vigor level of wheat seeds submitted to different sowing densities on seedling emergence, tillering and yield performance culture. The experiments were conducted in Londrina and Ponta Grossa, Paraná state, Brazil, with a completely randomized block design, in a 2x2x2 factorial scheme, with four replications. Two levels of seed vigor (high and low), two sowing densities (200 and 400 viable seeds per m2) and two wheat cultivars (BRS Sabiá and CD 150) were evaluated. The conducted tests were: seedling emergence, number of tillers, yield components, grain yield and apparent harvest index. The use of high vigor seeds helps the establishment of the plant stand and yield performance in both locations. The 400 seeds per m2 seedling density results in a lower number of tillers per plant in both locations. BRS Sabiá, in Ponta Grossa, has the highest grain yield.